Correction: Corrigendum: Adenylate kinase hCINAP determines self-renewal of colorectal cancer stem cells by facilitating LDHA phosphorylation - Yapeng Ji (Nature Portfolio, 2017)
Nature Communications 8: Article number:15308 (2017); Published: 18 May 2017; Updated: 16 June 2017 The original version of this Article contained an error in the spelling of the author Zemin Zhang, which was incorrectly given as Zeming Zhang. This has now been corrected in both the PDF and HTML versions of the Article.